Negotiation Between Customary Law and Islamic Law: The Practice of Palang Pintu in The Traditional Marriage in The Betawi Muslim Community - Al Farisi, Usman; Fakhrurazi, Fakhrurazi; Sadari, Sadari; Nurhadi, Nurhadi; Risdianto, Risdianto (De Jure: Jurnal Hukum dan Syari'ah, 2023)
In traditional Betawi weddings, there is usually a procession of the Palang pintu tradition—a negotiation attitude in Islamic law. This research was conducted to clarify the legal status of the Palang pintu tradition in the review of Islamic law so that people do not hesitate to follow it. This research uses a qualitative approach with 'urf theory and maslahah theory. The primary data were garnered from interviews, while the secondary data were sourced from fiqh literature, books related to marriage, and relevant research. The research findings show that the Palang pintu tradition has also experienced modern developments, affecting how the legal status is different. Since the Palang pintu tradition is considered contrary to the principles of the Islamic law that taught convenience in the past, there is a difference between Palang pintu from an Islamic point of view, specifically 'urf fasid and 'urf shahih, and it can be practiced. The difference between the previous palang pintu tradition and the current palang pintu tradition is that it is no longer burdensome or difficult, but rather easy.Keywords: marriage; palang pintu tradition; sustainable terms.